Anxiety-Disordered Adolescents With and Without a Comorbid Depressive Disorder: Variations in Clinical Presentation and Emotion Regulation. (September 2014) - Queen, Alexander H.; Ehrenreich-May, Jill
There is a high degree of comorbidity between anxiety and depressive disorders among treatment-seeking adolescents. Comorbid youth often present with greater diagnostic severity, worse social functioning, and more severe anxiety and depressive symptoms, compared with anxiety-disordered youth without depression. However, the degree to which these populations may differ in underlying affect and emotion regulation (ER) is largely unknown. This study compared 44 anxiety-disordered adolescents (ages 12-18 years) with a comorbid depressive disorder (ANX + DEP) and 32 anxiety-disordered adolescents without a comorbid depressive disorder (ANX) on several clinical and emotion-related variables. Results indicated that ANX + DEP adolescents were assigned higher clinician-rated diagnostic severity ratings, and reported greater functional impairment and more severe social anxiety and depressive symptoms, compared with ANX adolescents. In addition, ANX + DEP adolescents demonstrated higher levels of negative affect, lower levels of positive affect, and poorer self-reported and parent-reported ER. Implications for assessment and treatment, as well as directions for future research, are discussed.